Post-LGM dynamic deglaciation along the Victoria Land coast, Antarctica - Rhee, Hyun Hee; Lee, Min Kyung; Seong, Yeong Bae; Lee, Jae Il; Yoo, Kyu-Cheul; Yu, Byung Yong (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
The post-Last Glacial Maximum (LGM) deglaciation of Antarctica holds important clues for understanding past environmental changes and predicting future changes in the Antarctic Ice Sheet. Cosmogenic nuclide exposure dating of glacial erratics documents the spatial and temporal glacier changes during the most recent deglaciation. We collected 55 erratic cobbles from the eight glaciated benches on Inexpressible Island, which is at the terminal area of Priestley Glacier, Terra Nova Bay, Victoria Land, to elucidate its post-LGM deglaciation pattern. Analyses of the Be-10 ages and( 26)Al/Be-10 ratios suggest that Priestley Glacier underwent similar to 254 m of lowering during the mid-Holocene, between 8.9 and 5.9 ka. This lowering rate (similar to 0.09 m a(-1)) is faster than those observed along other Victoria Land outlet glaciers to the north (Tucker and Aviator), but slower than the one to the south (Mackay). The post-LGM lowering of these outlet glaciers was triggered by marine ice sheet instability, with their asynchronous onsets of deglaciation derived from their diachronous response times to the southwestward migration of the grounding-line retreat until their synchronous termination of deglaciation at similar to 6 ka. A post-LGM deglaciation model with the southwestward migration of the western Ross Ice Shelf grounding line provides the best match to the terrestrial exposure dating results of the thinning patterns of the outlet glaciers along the Victoria Land coast. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: TERRA-NOVA BAY; NUCLIDE PRODUCTION-RATES; GROUNDING-LINE RETREAT; ROSS SEA; COSMOGENIC NUCLIDES; ICE-SHEET; HISTORY; EROSION; BE-10; TEMPERATURE